New construction for older buildings : a design sourcebook for architects and preservationists - Smeallie, Peter H.; Smith, Peter H. K. (New York : John Wiley & Son, Inc., 1990)
This book is a survey of architectural attitudes toward the existing built environment. The wide range in the quality of the work, from excellent to routine, might be expected, but the geographic range of these projects is surprising, as is the amount of work by "signature" architectural firms.
Foreword -- Preface -- 1. Additions to buildings -- II. Altering the original -- III. Constructing anew amid old -- Index to professional firms -- Subject Index.
Includes bibliographical references and index.
Keywords: BUILDINGS -- REMODELING FOR OTHER USE